Intertoe Squamous Cell Carcinoma Developed in a Patient with Rheumatoid Arthritis under Etanercept Therapy - Efstathios Rallis; Vasiliki-Kalliopi Bournia; Constantinos Verros; Alexios Iliopoulos (Case Reports in Medicine)
The use of tumor necrosis factor-α (TNF-α) inhibitors in the treatment of various inflammatory conditions has altered the field of medical therapeutics. Squamous cell carcinoma is the second most common cancer of the skin, usually affecting sun-exposed areas of the body. We present here the case of a 75-year-old woman with rheumatoid arthritis, who developed an intertoe squamous cell carcinoma (SCC) of the right foot. According to her history, she received etanercept and methotrexate for 5 years for rheumatoid arthritis. The rare localization of this cancer could suggest a possible linkage of the malignancy to the chronic intake of anti-TNF-α treatment. This is the first reported case of an interdigital SCC developed under the use of an anti-TNF-α agent.